Flood risk assessment and its application in the eastern part of Dhaka City, Bangladesh. Issue 3 (4th November 2012) - Gain, A.K.; Hoque, M.M.
Abstract Traditional flood design methods are increasingly supplemented by risk‐oriented methods based on comprehensive risk analysis. This analysis requires: (1) the estimation of flood hazard that represents intensity of a flood, (2) estimation of vulnerability, e.g. percentage of damage to total property as a function of flood depth and duration, and (3) the consequences of flooding, e.g. loss of life and damage to property. In this study, flood hazard maps of the Balu‐Tongikhal River system within the eastern part of Dhaka City are prepared using geoprocessing tools and a hydrodynamic model. The raster‐based vulnerability maps and expected damage maps of several return period floods are then produced. In comparison with the classical inundation maps, these damage maps generate more information about the flooding events. Consequently, the produced maps are useful in evaluating policy alternatives and minimising property loss because of floods in the study area.